A numerical study on thin film flow and heat transfer enhancement for copper nanoparticles dispersed in ethylene glycol - Umer Hayat (17541777) (2023)
The current study examines thin film flow and heat transfer phenomena with some additional effects such as magnetohydrodynamic, viscous dissipation, and slip condition over unsteady radially stretching surfaces for various shapes of copper (Cu) nanoparticles dispersed in ethylene glycol (EG). The effective thermal conductivity of a nanofluid made of Cu nanometer-sized particles distributed in EGEG is significantly higher than that of pure EG. Partial differential equations are transformed into ordinary differential equations using the proper transformations. An effective convergent technique (i.e., BVP4C) is used to compute the solutions of nonlinear systems. MATLAB software is used to perform the calculations. The effect of numerous emerging physical characteristics on temperature and velocity, such as unsteadiness parameter (S), slip parameter (K), Hartmann number (M), solid volume fraction (ϕ), and Eckert number (EC) is investigated and illustrated graphically. The physical quantities, such as the skin friction coefficient and the Nusselt number, are calculated, described, and displayed in tabular form. It is observed that blade-shaped Cu nanoparticles had the lowest surface drag, highest heat transfer rate, and minimum film thickness compared to the brick and cylinder-shaped nanoparticles. According to our detailed investigation blade-shaped Cu nanoparticle is the most suited solution for manufacturing unsteady radially stretching modules. Other Information Published in: Reviews on Advanced Materials Science License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/rams-2022-0320